KEWENANGAN PERADILAN AGAMA DALAM PENYELESAIAN SENGKETA EKONOMI SYARIAH - Tuti Haryanti (IAIN Ambon, 2017)
The inception of Act RI No. 3, 2006 on the Religious Courts have strengthened position of Religious Courts as one of the law enforcement institution for the expansion of absolute competence in the resolution of Islamic economics dispute. However, after being passed of the legislation, many rules were also passed that indirectly unripe the authority of religious courts as an authorized institution to resolve the Islamic economics disputes. The norm conflicts occurred between some rules and regulation could not remove the authority of religious courts in resolving the Islamic economics disputes because it based on the Islamic principles. The courts are able to apply the Islamic principles and make the Qur'an, Hadith of Prophet, ijtihad of Islamic jurists as a guide in the court is only the religious courts. So it is a necessity, if the Islamic economic disputes resolved in the religious court because the whole is something has been attached to the Muslim community and moreover the religious courts id for the needs of Muslim community. Keywords: authority, religious courts, resolution of Islamic economics dispute